The Role of Hydrolyzed Oral Collagen Supplementation on Premature Aging in Women Aged 30-60 Years - Rianto, Louis; Hong, Moonly; Margaretha, Olivia; Edwin, Edward (Indonesian Journal of Global Health Research, 2024)
Collagen is an important substance in the body to compose connective tissue. One of the important roles of collagen is to keep the skin strong and elastic so that the skin does not look old. However, with age, the body's collagen production will decrease and have an effect on skin aging, so external collagen supplementation is often used to prevent premature aging. This study was conducted to review more deeply the role and effectiveness of oral hydrolyzed collagen supplementation in preventing premature aging of the skin of women aged 30-60 years and to compare the effectiveness and benefits of topical collagen compared to oral collagen so that the results of this study are expected to be useful in considering the use of oral collagen for prevention of premature aging. A literature search was conducted from journal articles with a time span of 2012-2022 using databases in the form of Pubmed, Ebsco, Google Scholar, Hindawi, Medline and Science Direct (28 articles). We included 28 research articles that met the inclusion and exclusion criteria by analyzing the abstract and full text through tables together. A literature search was conducted from journal articles with a time span of 2012-2022 using databases in the form of Pubmed, Ebsco, Google Scholar, and Science Direct. Research shows that hydrolyzed oral collagen has a fairly high level of effectiveness in inhibiting the premature aging process, in the form of increasing skin hydration and elasticity and reducing wrinkles in several areas of the face. The use of oral and topical collagen also has almost the same effect and will provide a more satisfying effect if consumed together.